Privity of Contract and Third Party Rights in European Construction Projects - Hällström, Benjamin af (fi=Turun yliopisto|en=University of Turku|, 2016)
Privity of contract has lately been criticized in several European jurisdictions, particu-larly due to the onerous consequences it gives rise to in arrangements typical for the modern exchange such as chains of contracts. Privity of contract is a classical premise of contract law, which prohibits a third party to acquire or enforce rights under a contract to which he is not a party. Such a premise is usually seen to be manifested in the doctrine of privity of contract developed under common law, however, the jurisdictions of continental Europe do recognize a corresponding starting point in contract law. One of the traditional industry sectors affected by this premise is the construction industry. A typical large construction project includes a contractual chain comprised of an employer, a main contractor and a subcontractor. The employer is usually dependent on the subcontractor's performance, however, no contractual nexus exists between the two. Accordingly, the employer might want to circumvent the privity of contract in order to reach the subcontractor and to mitigate any risks imposed by such a chain of contracts. From this starting point, the study endeavors to examine the concept of privity of con-tract in European jurisdictions and particularly the methods used to circumvent the rule in the construction industry practice. For this purpose, the study employs both a com-parative and a legal dogmatic method. The principal aim is to discover general principles not just from a theoretical perspective, but from a practical angle as well. Consequently, a considerable amount of legal praxis as well as international industry forms have been used as references. The most important include inter alia the model forms produced by FIDIC as well as Olli Norros' doctoral thesis "Vastuu sopimusketjussa". According to the conclusions of this study, the four principal ways to circumvent privity of contract in European construction projects include liability in a chain of contracts, collateral contracts, assignment of rights as well as security instruments. The contempo-rary European jurisdictions recognize these concepts and the references suggest that they are an integral part of the current market practice. Despite the fact that such means of circumventing privity of contract raise a number of legal questions and affect the risk position of particularly a subcontractor considerably, it seems that the impairment of the premise of privity of contract is an increasing trend in the construction industry.